Liquid Crystal Alignment on Polyurethane Layer Treated by Ion Beam Irradiation with Low Power Intensity. (25th May 2018) - Jeong, Hae-Chang; Kim, Eun-Mi; Heo, Gi-Seok; Lee, Ju Hwan; Kim, Dong Hyun; Lee, Dong Wook; Han, Jeong Min; Kim, Tae Wan; Seo, Dae-Shik
Abstract : The characteristics of ion beam (IB)-irradiated polyurethane (PU) alignment layer fabricated for use as liquid crystal (LC) alignment layer were investigated. Even at a low IB intensity of 600 eV, uniform LC alignment was achieved. The LC alignment on the IB-irradiated PU surface was attributed to surface polarities compared to C-C bonds in the PU substrate; hence, the van der Waals interactions between LC molecules and the PU surface were increased, thereby maintaining a good balance for homogeneous alignment. The LC cells based on PU irradiated with low intensity IB show potential for application as an alternative alignment layer in new LCD products.